Who decides, and how? preferences, uncertainty, and policy choice in the European Parliament - Ringe, Nils. (Oxford : Oxford University Press, 2010)
Despite a flourishing literature on the European Parliament, we know surprisingly little about the micro-foundations of its politics. This text addresses that shortcoming by examining how individual legislators make policy choices, how these choices are aggregated, and what role parties and committees play in this process.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Parliament; European Union countries -- Politics and government